Diagnosis, consultation, treatment, and impact of migraine in the US: Results of the OVERCOME (US) study - Lipton, Richard B.; Nicholson, Robert A.; Reed, Michael L.; Araujo, Andre B.; Jaffe, Dena H.; Faries, Douglas E.; Buse, Dawn C.; Shapiro, Robert E.; Ashina, Sait; Cambron‐Mellott, M. Janelle; Rowland, John C.; Pearlman, Eric M. (Headache, 2022)
Objective The ObserVational survey of the Epidemiology, tReatment and Care of MigrainE (OVERCOME; United States) study is a multicohort, longitudinal web survey that assesses symptomatology, consulting, diagnosis, treatment, and impact of migraine in the United States. Background Regularly updating population‐based views of migraine in the United States provides a method for assessing the quality of ongoing migraine care and identifying unmet needs. Methods The OVERCOME (US) 2018 migraine cohort involved: (I) creating a demographically representative sample of US adults using quota sampling (n = 97,478), (II) identifying people with active migraine in the past year via a validated migraine diagnostic questionnaire and/or self‐reported medical diagnosis of migraine (n = 24,272), and (III) assessing consultation, diagnosis, and treatment of migraine (n = 21,143). The current manuscript evaluated whether those with low frequency episodic migraine (LFEM; 0–3 monthly headache days) differed from other categories on outcomes of interest. Results Among the migraine cohort (n = 21,143), 19,888 (94.1%) met our International Classification of Headache Disorders, 3rd edition‐based case definition of migraine and 12,905 (61.0%) self‐reported a medical diagnosis of migraine. Respondents’ mean (SD) age was 42.2 (15.0) years; 15,697 (74.2%) were women. Having at least moderate disability was common (n = 8965; 42.4%) and around half (n = 10,783; 51.0%) had consulted a medical professional for migraine care in the past year. Only 4792 (22.7%) of respondents were currently using a triptan. Overall, 8539 (40.4%) were eligible for migraine preventive medication and 3555 (16.8%) were currently using migraine preventive medication. Those with LFEM differed from moderate and high frequency episodic migraine and chronic migraine on nearly all measures of consulting, diagnosis, and treatment. Conclusion The OVERCOME (US) 2018 cohort revealed slow but steady progress in diagnosis and preventive treatment of migraine. However, despite significant impact among the population, many with migraine have unmet needs related to consulting for migraine, migraine diagnosis, and getting potentially beneficial migraine treatment. Moreover, it demonstrated the heterogeneity and varying unmet needs within episodic migraine.